36grade 45' 38" +
24grade 32' 45"
Si transformarea
Răspunsuri la întrebare
Răspuns de
0
36hrade45'38''+24grade32'45''=36grade+45'+38''+24grade+32'+45''=
(36grade+24grade)+(45'+32')+(38''+45'')=60grade+77'+83''
=60grade+(60'+17')+(60"+23")=(60 grade+1grad)+(17'+1')+23"=61grade18'23''
(36grade+24grade)+(45'+32')+(38''+45'')=60grade+77'+83''
=60grade+(60'+17')+(60"+23")=(60 grade+1grad)+(17'+1')+23"=61grade18'23''
Răspuns de
0
36•45'38" + 24•32'45" = 60•77'83"=60•100'=61•40'
Alte întrebări interesante
Biologie,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
10 ani în urmă
Matematică,
10 ani în urmă
Matematică,
10 ani în urmă
Limba română,
10 ani în urmă